Benzimidazole-based DGAT1 inhibitors with a [3.1.0] bicyclohexane carboxylic acid moiety. Issue 10 (15th May 2019) - He, Shuwen; Lai, Zhong; Hong, Qingmei; Shang, Jackie; Reibarkh, Mikhail; Kuethe, Jeffrey T.; Liu, Jian; Guiadeen, Deodial; Krikorian, Arto D.; Cernak, Timothy A.; Dykstra, Kevin D.; Sperbeck, Donald M.; et al.
Graphical abstract: Previously disclosed benzimidazole-based DGAT1 inhibitors containing a cyclohexane carboxylic acid moiety suffer from isomerization at the alpha position of the carboxylic acid group, generating active metabolites which exhibit DGAT1 inhibition comparable to the corresponding parent compounds. In this report, we describe the design, synthesis and profiling of benzimidazole-based DGAT1 inhibitors with a [3.1.0] bicyclohexane carboxylic acid moiety. Our results show that single isomer 3A maintains in vitro and in vivo inhibition against DGAT1. In contrast to previous lead compounds, 3A does not undergo isomerization during in vitro hepatocyte incubation study or in vivo mouse study. Abstract: Previously disclosed benzimidazole-based DGAT1 inhibitors containing a cyclohexane carboxylic acid moiety suffer from isomerization at the alpha position of the carboxylic acid group, generating active metabolites which exhibit DGAT1 inhibition comparable to the corresponding parent compounds. In this report, we describe the design, synthesis and profiling of benzimidazole-based DGAT1 inhibitors with a [3.1.0] bicyclohexane carboxylic acid moiety. Our results show that single isomer 3A maintains in vitro and in vivo inhibition against DGAT1. In contrast to previous lead compounds, 3A does not undergo isomerization during in vitro hepatocyte incubation study or in vivo mouse study.